ANALISIS FAKTOR PENYEBAB DEGRADASI MORAL SOPAN SANTUN PADA SISWA KELAS V SD X GUGUK MALALO - Miftahul Jannah (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2023)
The purpose of this study is to describe the impact of moral degradation of manners in one of the public elementary schools located in Guguk Malalo. The approach used in this study is qualitative with a phenomenological research type. The subjects in this study were high school students at the primary school where the research took place. This research was conducted in the odd semester of 2022. Based on the results of the research, it was concluded that there was a decline in the moral courtesy of elementary school students at one of SD X located in Guguk Malalo. This can be seen from the results of research which shows that the causal factors of moral degradation in students are lack of attention from parents, wrong associations, and the influence of social media that is in the hands of students.